One new genus and six new species of Coraebini Bedel, 1921 (Coleoptera: Buprestidae) from the Philippines - Bellamy, C. L.; Ohmomo, Sadahiro (Zootaxa, 2011)
New Philippine Coraebini (Coleoptera: Buprestidae) are described: one new genus, Visayasella, gen. nov., is erected for two new species: the type species Visayasella superba sp. nov. from Leyte and V. gracilis sp. nov. from Negros. The new genus is contrasted to the genera Obenbergerula Strand 1932 (= Böttcheria Hoscheck 1931) and Sibuyanella Obenberger 1942 in a table of character states. Four new species of Toxoscelus Deyrolle 1864 are described from Leyte: Toxoscelus actenodes sp. nov., T. bichromoplagiatus sp. nov., T. circumscriptus, sp. nov. and T. griseovariegatus sp. nov. and contrasted with the two previously described Toxoscelus species from Luzon: T. acutipennis Fisher 1922 and T. rugicollis Saunders 1874 in a key. The six new species and several putatively related genera and species are illustrated in two color plates.